Analisis Pembentukan Karakter Melalui Lingkungan Sekolah SDN Tanjung Pura Kabupaten Tasikmalaya - Yulianti, Eva; Nurfirdaus, Nunu; Ropiah , Opah (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to find out the implementation of character formation, the role of the school environment in the formation, and the efforts made by teachers and principals in the formation of the character of SDN Tanjung Pura, Tasikmalaya Regency. This study uses a qualitative method using 13 research subjects. Data analysis is carried out by the stages of data reduction, data presentation, and conclusion drawing. Research results were obtained through observation, interviews and documentation. Observations were carried out by making direct observations at the research location regarding character formation through the school environment of lower class students at SD Negeri Tanjung Pura. The implementation of character education at SDN Tanjung Pura includes routine activities such as Dhuha prayers, reciting the Yasin Koran, and mutual cooperation. Spontaneous activities such as reprimands and non-physical punishment are also carried out to increase students' vigilance. School principals play a role in creating policies and facilities that support character education and become role models in discipline. Apart from teaching, teachers guide students in carrying out worship and instill discipline through example and direct guidance. A good school environment also supports the process of forming student character